The Holy Spirit in Pilgrims’ Itineraria (4th–7th centuries) - Paczkowski, Mieczysław Celestyn (Teologia i Człowiek, 2019)
The Cenacle on Mount Sion is the traditional site of the descent of the Spirit on the Apostles at Pentecost. This place in Christian thought and piety reflects the pattern of continuity. Cenacle has become the center of the Church of Jerusalem and the Judeo-Christian house of worship. In the 4th century, the Christian writers consider the Mt. Sion „cut off” from the community of believers. The sources show that the later references to this building indicate it as the „Church of the Apostles”. The Church’s theologians spoke about „Sion, Mother of all the Churches”. Mount Sion was the destination of pilgrimage. The place of the Cenacle on Mt Sion often is presented by the pilgrims and the liturgical texts. Next, to it, there was material evidence and descriptions of the visitors.